Utilization of Phylano (Physics Ludo Uno) as Learning Media to Improve Physics Learning Outcomes - Chandra Halim M. (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
Physics learning in schools is frequently hampered by lack of learning resources and learning approaches that are still monotonous and uninteresting. To address these issues, game-based learning media can be employed as alternative to improve student learning results. The goal of this study was to determine how game-based learning medium Phylano (Physics Ludo Uno) affected physics learning outcomes for MAN 1 Bener Meriah class XI students. The research approaches include a review of the literature, observation, and experimentation. The research type is experimental, and the research design is one pretest-posttest group design. Inferential statistics are used to analyze the data, which includes normality, linearity, and homogeneity tests before concluding with the Paired Sample T-test as a hypothesis test. Furthermore, the N-Gain test is used to assess the efficiency of the learning material. The results demonstrate that the data passed the prerequisite test and that there was a great disparity between the pretest and the posttest evaluations. The average pretest is 62.88, and the average posttest is 87.44, with an N-Gain test of 0.73 (high), indicating that Phylano (Physics Ludo Uno) has a remarkable effect on increasing physics learning outcomes, as indicated by improvements in learning outcomes and statistical tests.